THE NONMETALLIC COMPONENTS IMMERSION TEST OF THE FUEL LINE SYSTEM OF MOTOR VEHICLES WITH BIOSOLAR (B5) - Emi Yuliarita (Widyariset, 2015)
Biodiesel is a renewable alternative energy has now been used widely. The use of biodiesel in diesel fuel vehicles is the hope of anticipating  the needs of increasing diesel oil. This is  consistent with the national energy policy  where the energy mix by 2025 is expected to use alternative energy  can  reach 25%. However, biodiesel has solvent  properties as a good  enough  so that it will be able to influence the  non-metallic  components of   the fuel  line  system  of  motor  vehicles. In  this  study  conducted immersion  test  against non-metallic components  of  the fuel  line system  of  motor  vehicles  Isuzu Panter  which refers   to  the  test  method  SAE  1747  with  the  aim  to  see  the  nature  of the  fuel compatibility with the non-metal components. After soaking material characterization tests performed  by measuring the volume and weight. The results  showed  that  the use of 5% biodiesel  in diesel  fuel cause nonmetallic components undergo expansion/swelling  and contracts in particular rubber, plastic, and  cork. The  biggest  change  occurred  shrinkage of  71.4% on  the  rubber cap tank-solar, Rubber Tank Low – Solar is 28.6% and the Rubber Tank Up-Solar is 25.5% respectively in the phase after 100 hours  of  immersion.